Information Technology Predictor Variables and Employee Productivity in Commercial Banks - Pius U. Angioha; Chidiebere U. Enukoha; Rose U. Agba; Gerald U. Ikhizamah (Yayasan Ahmar Cendekia Indonesia, 2020)
The study examines the extent to which information technology predictor variables; knowledge of information technology, management support for the use of information technology; frequency of use of information technology and access to information technology relates to employees’ productivity in commercial banks. The survey research method was used to select 400 samples from 8 banks using purposive, proportional and random sampling techniques. The study area is Cross River state. Structured questionnaires were used to elicit information from the population under study. The reliability of the instrument was tested using Cronbach Alpha (ranging from 0.79 and 0.91). Data were analysed using multiple regression at 0.05 confidence level. Result revealed a statistical significant joint influence of all the predictor variables (Knowledge of information technology; Management support for the use of information technology; Frequency of use of information technology and access to information technology on commercial bank employees’ productivity. Based on the findings, the study recommends that Banks employ IT in a manner that meets the desired qualities of flexibility and scalability while exposing employees to regular training to keep abreast of innovations in information technology